EXPLAINING PUBLIC TRUST AS A CONSEQUENCE OF NEW GOVERNMENT ADMINISTRATION IN IMPLEMENTING HEALTH AND MEDICAL EDUCATION POLICIES - Meftah, Niusha; Pourkiani, Masoud (Revista Inclusiones, 2019)
The purpose of this study was to explain public trust as a consequence of new government administration (participation, accountability and citizen satisfaction) in implementing policies of the health and medical education system and providing an effective model in line with the general policies of the Islamic Republic of Iran. The present study was an applied, descriptive, surveycorrelation type, specifically based on structural equation modeling. The statistical population of research consisted of two groups: the first group included those who referred to the Ministry of Health. Availability sampling method was used for this group due to large size and limitations such as the specific research topic and the unwillingness of many of the respondents to complete the new government management and public trust questionnaires. The second group was selected using stratified sampling method based on the development indicators of the five provinces of the 31 provinces, the heads, deputies and directors of medical universities (N=223), medical treatment (N=245 people), government hospitals (N=192 people) and networks and health centers (N=162 people). The sample was 262 people using the Cochran formula which was increased to 400 according to the completion rate of the questionnaires. Data were gathered by library and field method and using a questionnaire whose content and structural validity as well as their internal consistency were verified using structural equation modeling at 95% confidence level. The results showed that there was a significant relationship between participatory public administration with citizens' satisfaction with the mediating role of accountability in the health and medical education system. Also, participatory management, accountability, and citizens’ satisfaction were significantly associated with general trust in health and medical education systems. In addition, public trust as a consequence of the new government management has a significant relationship with the implementation of the health and medical education policy.